PEMBELAJARAN LITERASI MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS V SEKOLAH DASAR - Nurdiyanti, Eko; Suryanto, Edy (PAEDAGOGIA, 2010)
This research aims at describing: (1) the carrying out of literacy teachinglearning; (2) the quality of literacy teaching learning; (3) the obstacles in literacyteaching learning; and (4) the efforts of solving the problems in literacy teachinglearning. The method used is qualitative descriptive method. The sources of data includeplaces and events, informants, and documents. The data collecting technique was conductedthrough observation, interview, and document analysis. Data triangulation,method triangulation, and reviewing informant were used in data validity test. Dataanalysis technique applied interactive analysis model. The research result showed that:(1) learning literacy was conducted through three steps namely planning, implementing,and evaluating; (2) most students achieved the criteria of minimum mastery score, 7.5.Students' daily mean score in reading and writing was 7.5.; (3) the obstacles faced inlearning literacy are (a) teacher and students got difficulties in developing writingactivities; (b) school program of reading and writing fondness didn't run well, (c) media,teaching infrastructure haven't been optimally provided. (4) there were some ways toovercome the problems: (a) giving more assignments on writing especially uprightcontinual handwriting, (b) giving more assignments on reading by providing more booksat school, (c) providing sufficient infrastructure at schools.